If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y = -2(3y + -7) Reorder the terms: 8y = -2(-7 + 3y) 8y = (-7 * -2 + 3y * -2) 8y = (14 + -6y) Solving 8y = 14 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 8y + 6y = 14 + -6y + 6y Combine like terms: 8y + 6y = 14y 14y = 14 + -6y + 6y Combine like terms: -6y + 6y = 0 14y = 14 + 0 14y = 14 Divide each side by '14'. y = 1 Simplifying y = 1
| -8-2w=11 | | 42-x=-50 | | 3c+15=1c+14 | | 184.52=2.31w+15.81 | | 7+0.14x=8 | | 4(r+9)= | | x(x+10)=50 | | -x+8y=-4 | | 2x+16=0.4x | | 6x+10+2x=-6 | | 2(12-8x)=4x-3 | | 2190+1527-2502-267= | | 6(x-6)+6=8x-6 | | n+12=-7 | | 15-4m=10 | | 3X=6(1-x) | | 9-8y=41 | | -3n+6-7n=19 | | x^2-12=20 | | 12+9(3z-2)-15z= | | 2(2X+3)(X-5)=0 | | -2x+5-x=17 | | (x+1)(x+1)=2(x+1) | | -16=d+12 | | 16+x=43 | | 1(2X+3)(X-5)=0 | | 0(2X+3)(X-5)=0 | | x^2-1.6x=0 | | 4(m+3)=2m+12 | | (2b-4)(3b+6)=0 | | 1.5+x=1725 | | -1(2X+3)(X-5)=0 |